A remote sensing study of active folding and faulting in southern Kerman province, SE Iran - Walker, RT (2006)
Geomorphological observations reveal a major oblique fold-and-thrust belt in Kerman province, S.E. Iran. The active faults appear to link the Sabzevaran right-lateral strike-slip fault in southeast Iran to other strike-slip faults within the interior of the country and may provide the means of distributing right-lateral shear between the Zagros and Makran mountains over a wider region of central Iran. The Rafsanjan fault is manifest at the Earth's surface as right-lateral strike-slip fault scarps and folding in alluvial sediments. Height changes across the anticlines, and widespread incision of rivers, are likely to result from hanging-wall uplift above thrust faults at depth. Scarps in recent alluvium along the northern margins of the folds suggest that the thrusts reach the surface and are active at the present-day. The observations from Rafsanjan are used to identify similar late Quaternary faulting elsewhere in Kerman province near the towns of Mahan and Rayen. No instrumentally recorded destructive earthquakes have occurred in the study region and only one historical earthquake (Lalehzar, 1923) is recorded. In addition GPS studies show that present-day rates of deformation are low. However, fault structures in southern Kerman province do appear to be active in the late Quaternary and may be capable of producing destructive earthquakes in the future. This study shows how widely available remote sensing data can be used to provide information on the distribution of active faulting across large areas of deformation. © 2006 Elsevier Ltd. All rights reserved.